歯槽骨萎縮症例に対しサンドイッチグラフト法により下顎臼歯部の骨造成を行った1例 - 遠藤, 寛則; 宮本, 日出雄; 長谷川, 和樹 (日本口腔外科学会雑誌, 2014)
We describe a patient who underwent bone augmentation for dental implant placement in the atrophic posterior mandible by sandwich osteotomy, focusing mainly on surgical technique. A 46-year-old woman was referred to our hospital because of alveolar bone atrophy in the posterior mandible. She had bone necrosis after the placement of three dental implants at a dental clinic. The patient hoped for dental rehabilitation supported by dental implants. Therefore, we performed bone augmentation by means of sandwich osteotomy with cancellous bone harvested from the iliac crest. The superior segment was elevated up to 7 to 8 mm after vertical and horizontal osteotomy. The graft bone was placed between the segment and the basal bone, and was then fixed with microplates. Although the patient had postoperative infection transiently, alveolar bone augmentation was accomplished successfully. Thirteen months after bone augmentation, two dental implantswere placed. At the 1 year 7 month follow-up after dental implant placement, the postoperative course was uneventful, with no bone resorption. This procedure was considered to be a very reliable and effective method for vertical bone augmentation in the atrophic posterior mandible.